Implementation Of Total Quality Management In Al-Qur'an Education - Muhlil Musolin; Fauzi Fauzi; Naily An Ngimatul Azka (At-Tarbiyat, 2022)
TPQ Hidayatul Mubtadien applies the Qiro'ati Method in teaching the Qur'an. TPQ Hidayatul Mubtadien, in managing its institution, implements Total Quality Management to produce quality graduates. This study aimed to determine the implementation of TQM in TPQ Hidayatul Mubtadien Jlamprang Wonosobo. This study uses qualitative methods and field research that focuses on the problem of implementing TQM in TPQ Hidayatul Mubtadien and the nature of analytical descriptive research. The research location is at TPQ Hidayatul Mubtadien which is on Jalan Karya Tralis 3 No. 1, Jlamprang Village, Wonosobo District, Wonosobo Regency. The research time is from November 2021 to February 2022. Data collection is done by interview, observation, and documentation. Data analysis using data documentation, data reduction, displaying data, and drawing conclusions. The results of this study indicate that TPQ Hidayatul Mubtadien applies the concept of Total Quality Management in managing the institution. TPQ Hidayatul Mubtadien implements the values ​​of TQM in managing institutions in the following ways: Focus on Customers, Obsession with Quality, Scientific Approach, Long-term commitment, Teamwork for continuous improvement, Education and Training, Controlled Freedom, and Unity of Purpose.